The B chromosome of Sorghum purpureosericeum reveals the first pieces of its sequence - Karafiátová, Miroslava; Bednářová, Martina; Said, Mahmoud; Čížková, Jana; Holušová, Kateřina; Blavet, Nicolas; Bartoš, Jan (Journal of experimental botany, 2021)
More than a century has passed since the B chromosomes were first discovered. Today we know much of their variability, morphology, and transmission to plant progeny. With the advent of modern technologies, B chromosome research has accelerated, and some of their persistent mysteries have since been uncovered. Building on this momentum, here we extend current knowledge of B chromosomes in Sorghum purpureosericeum to the sequence level. To do this, we estimated the B chromosome size at 421 Mb, sequenced DNA from flow-sorted haploid pollen nuclei of both B-positive (B+) and B-negative (B0) plants, and performed a repeat analysis on the Illumina raw sequence data. This analysis revealed nine putative B-specific clusters, which were then used to develop B chromosome-specific markers. Additionally, cluster SpuCL4 was identified and verified to be a centromeric repeat. We also uncovered two repetitive clusters (SpuCL168 and SpuCL115), which hybridized exclusively on the B chromosome under fluorescence in situ hybridization and can be considered as robust cytogenetic markers. Given that B chromosomes in Sorghum are rather unstable across all tissues, our findings could facilitate expedient identification of B+ plants and enable a wide range of studies to track this chromosome type in situ.
Keywords: genetické markery; In Situ Hybridization, Fluorescence; B chromosomes; mapování chromozomů; repeat analysis; Sorghum purpureosericeum; chromozomy rostlin; flow cytometry; hybridizace in situ fluorescenční; pollen nuclei; Chromosomes, Plant; Chromosome Mapping; cytogenetics; Sorghum; Genetic Markers